Exercise capacity in young adults after hematopoietic cell transplantation in childhood. Issue 2 (5th September 2017) - Öberg, Anders; Genberg, Margareta; Malinovschi, Andrei; Hedenström, Hans; Frisk, Per
Abstract : A symptom‐limited incremental cycle ergometer test was performed in 17 young adult patients treated with hematopoietic cell transplantation and total body irradiation for hematologic malignancies during childhood. These 17 young adult patients were compared with 17 sex‐ and age‐matched healthy control subjects. Assessments of pulmonary function, cardiac function, body composition, and levels of growth hormone were made. The median follow‐up was 17.7 years. Patients achieved 63.2% of the predicted peak workload, whereas controls achieved 96.1% ( P  < .001). All patients, but only 1 control, failed to achieve a peak workload >80% ( P  < .001). Fat‐free mass was significantly lower (43.5 vs 57.6 kg, P  < .001) and fat mass percentage was significantly higher (31.8% vs 24.2%, P  = .011) in the patients. The peak workload adjusted for fat‐free mass was significantly lower in the patients (3.3 vs 4.3, P  < .001). In the patients, peak workload correlated significantly with total lung capacity ( r  = .54, P  = .025). In summary, long‐term survivors have significantly decreased exercise capacity compared with healthy individuals. Together with their altered body composition, this may predispose them to cardiovascular disease. Abstract : Exercise capacity is significantly decreased in a group of young adults treated with hematopoietic cell transplantation in childhood when compared with a group of matched healthy volunteers.